2002
DOI: 10.1016/s0370-1573(01)00101-6
|View full text |Cite
|
Sign up to set email alerts
|

Coherent γγ and γA interactions in very peripheral collisions at relativistic ion colliders

Abstract: Due to coherence, there are strong electromagnetic fields of short duration in very peripheral collisions. They give rise to photon-photon and photon-nucleus collisions with a high flux up to an invariant mass region hitherto unexplored experimentally. After a general survey of the field equivalent photon numbers and photon-photon luminosities, especially for relativistic heavy ion collisions, are discussed. Special care needs to be taken to include the effects of the strong interaction and nuclear size in thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
369
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 429 publications
(375 citation statements)
references
References 265 publications
5
369
0
1
Order By: Relevance
“…2.7 of Ref. [16] and references therein). One difficulty in this approach is the correct choice of the cutoff parameter present in the expression for the photon spectrum.…”
Section: ͑2͒mentioning
confidence: 97%
“…2.7 of Ref. [16] and references therein). One difficulty in this approach is the correct choice of the cutoff parameter present in the expression for the photon spectrum.…”
Section: ͑2͒mentioning
confidence: 97%
“…(See Ref. [3][4][5] for reviews.) Such exclusive processes are characterized by a lack of additional detector activity and a large rapidity gap between the produced particles and outgoing beams.…”
Section: Introductionmentioning
confidence: 99%
“…In ultraperipheral collisions (UPCs) of heavy-ions at impact parameters larger than twice the nuclear radius, where no nucleon-nucleon collisions occur, a strong flux of photons is generated that can be used for high-energy photoproduction (γ A, γ γ ) studies, as shown schematically in figure 1.19 [130][131][132]. The equivalent photon spectrum flux in UPCs increases with Z 2 /E γ and, thus, for Pb there is a Z 2 ∼ 7000 enhancement factor compared to electron or proton beams.…”
Section: Electromagnetic Pbpb Interactions: High-energy Photoproductionmentioning
confidence: 99%
“…At the LHC, the strong electromagnetic field due to the coherent action of the Z = 82 proton charges of the lead nucleus accelerated at TeV energies generates an equivalent flux of photons which can be used for high-energy photoproduction studies (see e.g. [130][131][132]). The equivalent (Weiszäcker-Williams) photon spectrum of UPCs has a ∝ Z 2 /E γ dependence and, thus, for a Pb beam, a Z 2 ≈ 7000 flux enhancement factor is expected compared to electron or proton beams.…”
Section: Introductionmentioning
confidence: 99%